Bilingual Dictionaries: Their Importance and Role in Learning Other Languages: المعاجم الثنائيّة اللّغة: أهميتها ودورها في تعلّم اللّغات الأخرى - TARECHE, Djemoi; SOUAKER, Ibrahim (Maalim, 2025)
Bilingual dictionaries rank among the most widely used reference tools in the modern lexical industry, because of the wide range of services they offer to the users. They are indispensable for learning foreign languages, as they serve as a bridge between the source language and the target language, making the learning process smoother and more effective, especially for beginners. This made them widely known among learners and students of various backgrounds and levels. They have appeared in different forms (print-electronic), and their importance has further increased due to the tremendous technological advancements that have significantly contributed to their modernization and digitalization. Consequently, major institutions have been working at a rapid pace to produce and publish this type of dictionary in service of their national languages. In this research paper, we seek to shed light on the concept of the bilingual dictionary, outline its types and categories, identify the essential information it should contain, highlight its importance in language learning, and explore its relationship to the field of computing and its role in translation.